PEMARKAH LEKSIKAL PEMBENTUK MAKNA PRAGMATIK IMPERATIF DALAM KALIMAT INTEROGATIF BAHASA INDONESIA (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis research examines the lexical markers pragmatic imperative meaning formulation included in interrogative sentences Indonesian language. The aim of this research was to formulate lexical markers pragmatic imperative meaning formation from interrogative sentences Indonesian language. Problems in this research answered through structural and pragmatics theory. The data in this research were taken from six teens novels Indonesian language. The method used was a qualitative method with descriptive data. The data were analyzed using agih and pragmatic frontier techniques. Based on data analysis that has been done, lexical markers included of question words, negative question words, and affirmative command words. Markers in form of question words were apa, siapa, kenapa/mengapa, gimana/bagaimana, kapan, sejak kapan, sampai kapan, mana, mana bisa, mana boleh, di mana, ke mana, dari mana, and berapa. Markers in form of negative question words were tidak, tak, takkan, and nggak. Markers in form of affirmative commands were bisa, mau, coba, boleh, ayo, and yuk.Keywords: lexical markers, pragmatics imperative meaning, interrogative sentences, question words